2016
DOI: 10.1007/s11011-016-9932-9
|View full text |Cite
|
Sign up to set email alerts
|

HBK-14 and HBK-15 with antidepressant-like and/or memory-enhancing properties increase serotonin levels in the hippocampus after chronic treatment in mice

Abstract: 5-HT1A and 5-HT7 receptor ligands might have antidepressant-like properties and improve cognitive function. We previously reported significant antidepressant- and anxiolytic-like effects of two dual 5-HT1A and 5-HT7 receptor antagonists in various behavioral tests in rodents. As a continuation of our previous experiments, in this study we aimed to investigate whether chronic administration of 1-[(2,6-dimethylphenoxy)ethoxyethyl]-4-(2-methoxyphenyl)piperazine hydrochloride (HBK-14) and 1-[(2-chloro-6-methylphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
(53 reference statements)
5
15
0
Order By: Relevance
“…Since HBK-14 is stronger 5-HT 7 receptor antagonist, its anxiolytic-like effect might be more profound. These findings are consistent with our previous experiments, where we demonstrated that among the two, HBK-14 possessed stronger anxiolytic-like properties, whereas HBK-15 antidepressant-like activity [ 21 , 22 ]. The second explanation is simply the difference in bioavailability—HBK-14 has lower bioavailability, and this might underlie the lack of antidepressant-like effect.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Since HBK-14 is stronger 5-HT 7 receptor antagonist, its anxiolytic-like effect might be more profound. These findings are consistent with our previous experiments, where we demonstrated that among the two, HBK-14 possessed stronger anxiolytic-like properties, whereas HBK-15 antidepressant-like activity [ 21 , 22 ]. The second explanation is simply the difference in bioavailability—HBK-14 has lower bioavailability, and this might underlie the lack of antidepressant-like effect.…”
Section: Discussionsupporting
confidence: 93%
“…Our previous experiments revealed that chronic treatment with HBK-15 increased serotonin level in the hippocampus [ 22 ]. Serotonin, at least partially, regulates the level of neurotrophins in the central nervous system [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations